The role of multinational companies in attracting foreign direct investment to developing countries (UAE as a model) - M. Bakr Hamid Jasoum (Scholar Express Journals, 2023)
Multinational corporations are a huge economic force through the huge investments they make in the global economy. They have become an important center and a basic driving force for the global economic and political system through their influence in making economic, social and .political events and transformations in the world The study aimed to clarify the impact of multinational companies in attracting foreign direct investment to developing countries, including the UAE, based on the hypothesis that these companies are the main gateway to attracting foreign direct investment, as their investments and expansion of their activities had several positive effects such as creating new job opportunities and obtaining advanced technology. In addition to obtaining an increase in complementary relations in various sectors, the study concluded that foreign direct investment has become a global phenomenon that various countries are working to obtain, as the United Arab Emirates topped the Arab countries in incoming foreign investment, amounting to (13787) million dollars in the year (2019) due to Availability of an appropriate investment climate, advanced infrastructure, the establishment of many free and specialized industrial zones, in addition to its expansion through privatization operations .and business-friendly legislation
Keywords: industrial; expansion; various; climate